Teachers Interpretive Understanding of Student Agency within Flexible Learning Ecosystems - I Ketut Surata (PT FORMOSA CENDEKIA GLOBAL, 2026)
The shift toward flexible learning ecosystems requires teachers to navigate complex pedagogical dynamics in which differentiation, technology integration, and diverse student needs place student agency at the center of learning. This study explores how teachers interpret student agency—reflected in learners’ choices, decisions, and independence—and how these interpretations shape pedagogical strategies in adaptive learning environments. Using an interpretive qualitative approach with Interpretative Phenomenological Analysis, data were collected through semi-structured interviews with six teachers from three senior high schools in Bali implementing curriculum flexibility and differentiated instruction. The findings show that teachers’ understandings of student agency evolve from a normative view to a contextual construction, conceptualizing agency as a combination of learner independence, decision-making capacity, and reflective ability. This shift is influenced by student readiness, institutional support, and teachers’ professional experience. The study confirms that student agency is a dynamic construct shaped by interactions between responsive pedagogy and flexible learning environments, contributing to the development of autonomy-oriented learning design in secondary education.